A guide to selecting high-performing antibodies for STING1 (Uniprot ID: Q86WV6) for use in western blot, immunoprecipitation, and immunofluorescence [version 2; peer review: 2 approved] - Vera Ruíz Moleón; Carl Laflamme; Kathleen Southern; Riham Ayoubi; Charles Alende; Maryam Fotouhi (F1000Research)
Stimulator of interferon genes protein (STING1) is an immune adaptor protein which promotes innate immune defense mechanisms against pathogens. To enhance our understanding of STING1-associated disease, it is essential to make high-performing antibodies accessible to the scientific community. This study aims to improve reliability of STING1 research as we have characterized sixteen STING1 commercial antibodies for western blot, immunoprecipitation, and immunofluorescence using a standardized experimental protocol based on comparing read-outs in knockout cell lines and isogenic parental controls. These studies are part of a larger, collaborative initiative seeking to address antibody reproducibility issues by characterizing commercially available antibodies for human proteins and publishing the results openly as a resource for the scientific community. While use of antibodies and protocols vary between laboratories, we encourage readers to use this report as a guide to select the most appropriate antibodies for their specific needs.